EMOTIONAL INTELLIGENCE, PERCEPTIONS OF ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL CLIMATE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Ressa Indah Sari; okki trinanda (Human Resource Management Studies, 2022)
This research analyzes (1) the influence of Emotional Intelligence on Organizational Citizenship Behavior at PT. Bank Pembangunan Daerah Sumatera Barat Lubuk Alung Branch (2). The influence of Perceived Organizational Support on Organizational Citizenship Behavior at PT. Bank Pembangunan Daerah Sumatera Barat Lubuk Alung Branch (3). The influence of Organizational Climate on Organizational Citizenship Behavior at PT. Bank Pembangunan Daerah Sumatera Barat Lubuk Alung Branch . This research is a causal research. The population in this study were all employees of PT. Bank Pembangunan Daerah Sumatera Barat cabang Lubuk Alung with total 52 people. The sampling technique in this study is Total Sampling, where the number of samples is the entire population.. Collecting data using a questionnaire with a Likert scale. The analysis technique used is Multiple Linear Regression through SPSS Ver Software. 22.0 This study resulted in (1) positive and significant influence of emotional intelligence on Organizational Citizenship Behavior. (2) positive and significant influence of Perception of Organizational Support on Organizational Citizenship Behavior. (3) positive and significant influence of organizational climate on Organizational Citizenship Behavior